Pengaruh Pendidikan Vokasi dan Link and Match terhadap Kesiapan Kerja Pemuda di Kota Cimahi - Delia subrayanti; Dyah Bayu Framesthi; Hendriady de Keizer; Priatna Kesumah; Yusar Firmansyah; Zira Durun Nafisah; Neng Rohaeni (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2026)
The high rate of youth unemployment in Cimahi City indicates a structural problem in the transition from education to the workforce. Vocational education, which is expected to be a solution to provide a ready-to-use workforce, has not fully met the needs of the industrial and business world (IDUKA). This study aims to analyze the effect of vocational education and the implementation of link and match on the work readiness of youth in Cimahi City. The research method used a mixed methods approach with a sequential explanatory design, combining a quantitative survey of the young workforce and qualitative interviews with education and industry stakeholders. The results show that vocational education has a positive effect on work readiness, but this effect is still in the moderate category due to the weak relevance of the curriculum and limited industry involvement. The implementation of link and match has proven to be a determining factor in improving work readiness, especially through internship experiences, industry-based training, and competency certification. This study concludes that strengthening systemic collaboration between the local government, vocational education, and IDUKA is key to improving youth work readiness and reducing the competency gap in Cimahi City.